Effect of physicians' gender on communication and consultation length: a systematic review and meta-analysis. (October 2013) - Jefferson, Laura; Bloor, Karen; Birks, Yvonne; Hewitt, Catherine; Bland, Martin
Objective: Physician gender may be a source of differences in communication between physicians and their patients, which may in turn contribute to patient satisfaction and other outcomes. Our aim was to review systematically research on gender differences in the length, style and content of communication with patients. Methods: Seven electronic databases were searched from inception to September 2010 with no language restrictions (included MEDLINE; PsychINFO; EMBASE; CINAHL; Health Management Information Consortium; Web of Science; and ASSIA). 'Grey' literature was also searched. Data extraction and quality assessment was carried out in accordance with Cochrane Collaboration guidelines by at least two reviewers. The review uses mainly narrative synthesis due to the heterogeneous nature of the studies, with only data on consultation length being pooled in a random effects generic inverse variance meta-analysis. Results: Searches yielded 6412 articles, of which 33 studies fulfilled the inclusion criteria. Studies were heterogenous and of mixed quality. Conflicting results are reported for many communication variables. There is some evidence that female physicians adopt a more partnership building style and spend on average 2.24 min longer with patients per consultation (95% CI 0.62–3.86) than their male colleagues. Conclusions: Greater patient engagement by female doctors may reflect a more patient-centred approach, but their longer consultation times will limit the number of consultations they can provide. This has implications for planning and managing services.